LOAN SETTLEMENT MECHANISM AT PT. BANK SUMSEL BABEL BELITANG BRANCH - Carneza, Fency; Hardiyanti, Siti Epa (Management Science Research Journal, 2023)
Bank is a business entity that collects funds from the public in the form of savings and distributes them back to the community in the form of credit and or other forms in order to improve the standard of living of the people at large. The role of banking in the economic development of a nation is very important, like a heart in the human body. The banking business includes three activities, namely collecting funds, distributing funds, and providing other bank services. The activity of collecting and distributing funds is the main activity of the bank, while providing other bank services is only a supporting activity. Activities to raise funds are in the form of collecting funds from the public in the form of savings deposits, current accounts, and time deposits. Activities distribute funds in the form of lending to the community. Meanwhile, other banking services are provided to support the bank’s main activities. Bank Sumsel Babel has a role as a source of regional income, and runs its business as a commercial bank whose function is to provide banking services and help improve people’s living standards. One of the special services at Bank Sumsel Babel Belitang Branch is the provision of consumer credit in the form of KSG credit (Multipurpose Credit) for active employees whose salaries have been distributed through the bank in accordance with the cooperation agreement. Multipurpose Credit (KSG) for debtors with active employee status who will enter retirement until the debtor retires, for retirees themselves or widows/widowers whose retirement benefits have been distributed through a bank where the source of the return comes from the debtor’s pension benefits, guaranteed by a Decree (SK) Employees. Basically, credit can be given to anyone who has the ability, but in this KSG credit (Multipurpose Credit) it can only be given to prospective debtors who have a fixed income. When the debtor and creditor have implemented the credit agreement, the debtor can receive the agreed amount of money. However, in reality, the easier it is to provide credit services to the public, it tends to become a serious problem in paying these credits. The problem will be seen in the payment of installments in the following months, because the obligations that must be paid are not carried out in accordance with the mandatory principal stated in the installments